MODEL FOR LEAN SERVICE MEASUREMENT MANAGEMENT IN PRIVATE UNIVERSITIES OF NORTH SUMATERA - FAHMI SULAIMAN; Robbi Rahim; Jihan Sulaiman; Raja Intan Zarina Binti Raja Zaki Hashim (Smart Education, 2025)
Abstract: The research uses qualitative and quantitative analysis approaches. The focus of the research is to develop a decision support system (DSS) that uses six main criteria: academic service quality, administrative service quality, availability of facilities and infrastructure, time management efficiency, student satisfaction, and waste reduction. Data were collected through observation, interviews and questionnaires distributed to 67 private universities in the LLDIKTI Region I North Sumatra as research samples. The collected data were processed according to the steps of the AHP-TOPSIS model. The results of this study are Academic services in first place with a weight of 0.78, Administrative services in second place with a weight of 0.72, Library & IT in third place with a weight of 0.65, Campus facilities in fourth place with a weight of 0.58, and Financial & payment services in fifth place with a weight of 0.49.Keywords: Lean Servive; Measurement; Management; Academic; Service Quality